Molecular markers for characterization and conservation of plant genetic resources - DAR, AEJAZ AHMAD; MAHAJAN, REETIKA; SHARMA, SUSHEEL (The Indian Journal of Agricultural Sciences, 2019)
For properly understanding the molecular basis of phenotypic variation, accelerating breeding programmes and exploiting genetic resources of a particular crop, there is a need to explore the genome of the crop. Earlier conventional methods (phenotyping) were used by the breeders for identification and conservation of genetic resource. The conventional method is laborious for assignment of known and unknown plant taxa. Thus, to overcome the limitation of the conventional method, scientists developed molecular marker systems for conservation of genetic resources. The main aim of using molecular markers is to detect genetic variation in DNA sequence within and among the species. Molecular markers also find their role in producing new sources of genetic variation by introduction of advanced and useful traits from related species. From last two decades, different molecular markers were used for genetic analysis of crops. These markers include hybridization based markers (RFLP), PCR based markers (RAPD, AFLP, SSR, ISSR, SCAR, SRAP, SCoT) and sequence based markers (SNP, DArT, NGS). Besides many genes in chloroplast, mitochondria and ribosomes act as molecular markers that are useful for the phylogenetic studies and DNA barcoding of plants. This review provides an overview of the different molecular systems and their utilization in improving crop yield and productivity and conserving genetic resources.